Islam Menjunjung Tinggi Hak Asasi Manusia (Kajian Mendalam Kitab Al-Muwafaqat Karya Imam Al-Syathibi) - Imam Sucipto (ISLAMICA, 2015)
Human rights are natural rights. The right of every person and can't be revoked. All countries and people should be able to accept the concepts of human rights, because the formulation has been enhanced by adopting a different cultural and religious diverse nation. Islamic Shari'a itself has a purpose that is consistent with the principles of human rightsThe purpose of Islamic law or maqashid al-syari'ah contains the five most fundamental rights which is a primary need -dhoruriyat al-khoms- namely the right to live, reasonable maintenance, guard the descendants, the recognition of property rights and freedom of religion. The Prophet himself in leading the people of Medina had applyed the principles of these rights. There are more similarities than differences between the international human rights principles, with the national principles of human rights based on Islamic perspective.